Nivel de satisfacción con respecto a la atención recibida en pacientes médico-quirúrgicos hospitalizados en la Unidad de quemados, del Hospital Regional Isidro Ayora de Loja, durante el periodo mayo-octubre 2014 - Garcia Quinde, Mateo (2014)
In the last decade there has been a boom in studies to promote citizens who use health services, a feeling of pleasure with the care received. The quality of the doctor-patient relationship has been considered as an influential factor in the outcome of health care. The immediate effect of this is that the result of health care today is measured in terms of effectiveness, efficiency, patient perception of their pain or their independence, sense of physical and mental wellbeing and also its satisfaction with the results achieved. This prospective, descriptive, cross-sectional study, whose main objective is to know the level of satisfaction in medical and surgical patients in the Burns Unit of the Regional Hospital "Isidro Ayora" Loja, identifying their perceptions of the attributes of quality of care in health and the factors of satisfaction and dissatisfaction, obtaining favorable results in most aspects valued Keywords: Satisfaction, Atention, Patient.